«A vueltas con la progresión narrativa en la lírica gallego-portuguesa. ¿Una secuencia en las Cantigas de Sancho Sanchez, clérigo?» - Pousada Cruz, Miguel Ángel (Revista de Literatura Medieval, 2016)
Resumen: Los apógrafos renacentistas B y V conservan un conjunto de cinco cantigas de amigo y una cantiga de amor que son atribuidas, a la luz de las rúbricas atributivas y de la Tavola colocciana, al clérigo Sancho Sanchez. En este trabajo se analiza la posible existencia de una secuencia narrativa entre esas seis composiciones, tras una lectura y un atento análisis de los textos. Palabras clave: Sancho Sanchez, clérigo, secuencia narrativa, secuencia lírica, progresión narrativa, lírica profana gallego-portuguesa. «Rethinking the narrative progression in Galician-Portuguese lyric poetry. Is there a sequence in the cantigas by Sancho Sanchez, clérigo?» Abstract: The Renaissance apographs B and V preserve a collection of five cantigas de amigo and a cantiga de amor attributed to the clergyman Sancho Sanchez, in the light of the identifying rubrics and the tavola by Colocci. The aim of this paper is to analyze the possible existence of a narrative sequence among the aforementioned six verses, following a detailed reading and examination of the poems. Keywords: Sancho Sanchez, clérigo, narrative sequence, lyric sequence, narrative progression, Galician-Portuguese prophane lyric poetry.